Polysulfone Photocatalys Membrane Effects Of Catalyst Polymeric Additives And Molecular Imprint For Selective Filtration And Photodegradation - Melvin, Ng Hau Kwan (2017)
Photocatalytic membranes exhibit great potential for wastewater treatment since they can combine filtration and photo degradation in a single unit. In this work, 2 wt % poly(vinyl alcohol) (PVA) and polyvinyl pyrrolidone (PVP) were used to stabilize 2 wt % of photocatalytic nanoparticles (TiO2, Mn-TiO2 and ZnO) blended into polysulfone (PSf) membrane before phase inversion. These additives affect the formation of finger-like pores as shown in the SEM images. Blending PVA and photocatalysts into PSf membrane resulted in significant improvement of humic acid (HA) rejection. The incorporation of PVP and photocatalysts into PSf membrane caused great improvement in water permeability, about 15.5~18.1 times higher than pure PSf membrane. Membranes with excellent rejection and permeation were further examined in photodegradation test, where PSf/PVP/photocatalyst showing < 15 % reduction in their photodegradation in comparison to the free nanoparticles. Pure TiO2 nanoparticles was further modified using molecular imprinting polymer (MIP-TiO2) before blending into PSf membrane. MIP-TiO2 achieved a photodegradation selectivity of methylene blue/methylene orange (MB/MO) up to 2.06 under UV irradiation for 1 h. MIP-TiO2 could be used in long duration (2 h) and up to 5 cycles of photocatalytic degradation with MB/MO selectivity of 2.16. The blending of MIP-TiO2 into PSf/PVP/MIP-TiO2 membrane further enhanced permeate flux up to 14.08 L/m2.h.bar, while retaining the major foulant MB with a selectivity of 2.83 under UV.